Measuring economic well-being and sustainability: A practical agenda for the present and the future - Peter J. van de Ven (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2019)
Gross domestic product (GDP) is the most widely used indicator from the system of national accounts. Although often interpreted as an indicator for (economic) well-being, it first and foremost monitors economic activity, and falls short of reflecting broader measures which try to capture well-being of people and sustainability. In 2009, the Stiglitz-Sen-Fitoussi Commission, in its Report on the Measurement of Economic Performance and Social Progress, put forward a number of recommendations to address this apparent disconnect. The report has been an important driver of the statistical agenda of the Organisation for Economic Cooperation and Development (OECD).This paper provides an overview of the main initiatives at the OECD in the context of national accounts. First it discusses work within the current system of national accounts, by giving more prominence to households. Going beyond the current system of national accounts, the paper addresses issues related to the impact of unpaid household activities on traditional measures of economic activity and to sustainability, tackled by implementing the System of Environmental Economic Accounts (SEEA). The paper ultimately proposes a broader accounting framework that goes well beyond the traditional macroeconomic framework of national accounts and that tries to establish a link with well-known initiatives to monitor well-being at large via for example the OECD Better Life Index.
Keywords: E01; E61; I30; I31; M41; Q50; 330; (economic) well-being; environmental-economic accounting; GDP; national accounts; sustainability